2014
DOI: 10.1371/journal.pone.0096028
|View full text |Cite
|
Sign up to set email alerts
|

Fish with Chips: Tracking Reef Fish Movements to Evaluate Size and Connectivity of Caribbean Marine Protected Areas

Abstract: Coral reefs and associated fish populations have experienced rapid decline in the Caribbean region and marine protected areas (MPAs) have been widely implemented to address this decline. The performance of no-take MPAs (i.e., marine reserves) for protecting and rebuilding fish populations is influenced by the movement of animals within and across their boundaries. Very little is known about Caribbean reef fish movements creating a critical knowledge gap that can impede effective MPA design, performance and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 47 publications
1
84
0
Order By: Relevance
“…Eighteen species of acoustically tagged reef fishes in the Caribbean region showed fidelity to marine protected areas (MPAs). However, three-quarters of the species examined travelled outside their protective limits (61). In contrast, telemetry data for five historically overfished snapper and grouper species in the Dry Tortugas islands indicated that the fish stayed primarily in a no-take marine reserve, which should provide sufficient protection for species recovery (Fig.…”
Section: Scaling From Individual To Multispecies Movementsmentioning
confidence: 97%
“…Eighteen species of acoustically tagged reef fishes in the Caribbean region showed fidelity to marine protected areas (MPAs). However, three-quarters of the species examined travelled outside their protective limits (61). In contrast, telemetry data for five historically overfished snapper and grouper species in the Dry Tortugas islands indicated that the fish stayed primarily in a no-take marine reserve, which should provide sufficient protection for species recovery (Fig.…”
Section: Scaling From Individual To Multispecies Movementsmentioning
confidence: 97%
“…To that aim, coastal and estuarine Marine Protected Areas could efficiently allow for the protection of essential nursery habitats (Mesnildrey et al, 2013) As many species present both a similar dependence to coastal and estuarine nursery grounds (Seitz et al, 2014) and a moderate dispersion along the life cycle (Pittman et al, 2014), these insights from flatfish case studies could be considered of more general interest and significance across fish taxa.…”
Section: Consequences For Flatfish Population Dynamics and Insights Fmentioning
confidence: 99%
“…Grober- Dunsmore et al 2007, Planes et al 2009, Alós et al 2011. As populations inside reserves can be influenced by the movements of individuals, information on the spatial scales of adult movement and propagule dispersal is critical for the design of effective MPAs (Mora et al 2006, Grüss et al 2011, Pittman et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…algae, mollusks, crustaceans, and fishes). Generally, the home ranges of large herbivorous and predatory fishes cover several km 2 (Palumbi 2004, Sale et al 2005, Pittman et al 2014. Chateau & Wantiez (2009) used acoustic telemetry to study the movement patterns of 4 commercially important reef fish species among 3 reefs, one within an MPA (8.5 km 2 ) and the other 2 outside the MPA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation